Assessment of clathrate hydrate phase equilibrium data for CO2+CH4/N2+water system - Eslamimanesh, Ali; Babaee, Saeedeh; Gharagheizi, Farhad; Javanmardi, Jafar; Mohammadi, Amir H.; Richon, Dominique (Fluid Phase Equilibria, 2013)
Outlier diagnostic in phase equilibrium data of binary clathrate hydrates containing CO2 is the main aim of the present work. The treated experimental data are concerning the clathrate hydrates of CO2 + CH4/N2 in the presence of water. The utilized algorithm applies the basis of a mathematical approach, in which the statistical Hat matrix, Williams plot, and the residuals of two models results bring about the probable outliers detection. The range of applicability of the applied models and quality of the existing experimental data are also investigated. The van der Waals and Platteeuw (vdW–P) solid solution theory is used to model the hydrate phase, and the Valderrama–Patel–Teja equation of state (VPT-EoS) along with the non-density dependent (NDD) mixing rules is applied to deal with the fluid phases in the first model. The compositions of the vapor phase in equilibrium with gas hydrate and liquid water as well as the equilibrium pressures are predicted through the mentioned model. The second model includes a correlation proposed by Adisasmito et al., which is utilized to represent the hydrate dissociation pressures for three-phase equilibrium conditions (liquid water–vapor–hydrate). It is interpreted from the obtained results that the applied models for calculation/estimation of the phase behavior of the investigated binary clathrate hydrate systems have wide ranges of applicability. Consequently, we may, with high confidence level, say that among all data treated, one experimental equilibrium pressure value and four experimental hydrate dissociation values are probable doubtful ones.